What will prevail within citybreak travel, motivation or demotivation? Case study of Novi Sad, Vojvodina, Serbia - Vujicic, Miroslav D.; Stamenkovic, Igor Lj.; Stankov, Ugljesa; Kovacic, Sanja; Vasiljevic, Djordjije; Popov Locke, Jasmina (Geographica Pannonica, 2020)
The aim of this paper is to develop a new perspective on urban tourist motivations and demotivation’s by applying the Analytic Hierarchy Process (AHP) model in order to better understand how tourists make decisions about which destinations to visit. Authors discovered that most important factor within city break travel is internal force, followed by the external force and least important is demotivation. The paper argues that the results indicate the value of applying the AHP model to understand the role and importance both of push and pull factors and demotivators in urban tourism destination choice.